(untitled) (Research, Society and Development, 2020)
Introduction: Antibiotics are drugs that have revolutionized the treatment of infectious diseases caused by bacteria and have reduced worldwide rates of morbidity and mortality associated with bacterial infections. Microorganisms are widely distributed in nature and can invade the human body causing infections. Currently, one of the biggest problems is the high resistance of these pathogens to antimicrobials. Objective: General objective to demonstrate how the impact of resistant bacteria and the indiscriminate use of antibiotics in the hospital environment and as specific objectives, find out how bacterial resistance develops. Methodology: A search was carried out by searching the databases: Lilacs, Google Scholar and Pubmed. Results and discussion: Bacterial resistance should be the subject of more research, as it has been growing at a faster pace than the discovery of new antimicrobial drugs. According to the search strategies, a total of 168 articles were found in the databases selected for the search. Conclusion: We conclude, then, that resistance, especially in front of the strains of staphylococcus represented throughout the work, are serious threats to cure infectious diseases and it is necessary to expand research focusing on the discovery of new drugs with antimicrobial action.